2001
DOI: 10.1116/1.1340010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of back contact on field emission from carbon films deposited by very high frequency chemical vapor deposition

Abstract: The effect of material and surface morphology of the back contact on field emission has been studied in carbon films deposited by very high frequency chemical vapor deposition at low temperature. The emission current was measured as a function of applied field for carbon films deposited simultaneously on various substrates coated with metals having different work functions ͑Ti, Cu, Ni, and Pt͒. Different metals demonstrated different types of microstructure and surface morphology. Therefore, the effect of back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…A detailed report on this will be presented else were. Recently Koserev et.al [23] have reported the effect of back contact on field emission from carbon films grown using very high frequency chemical vapour deposition at low temperature. They observed that there is no direct correlation between the contact metal work function and the emission current.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed report on this will be presented else were. Recently Koserev et.al [23] have reported the effect of back contact on field emission from carbon films grown using very high frequency chemical vapour deposition at low temperature. They observed that there is no direct correlation between the contact metal work function and the emission current.…”
Section: Resultsmentioning
confidence: 99%